If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12+5x=22+3x*
We move all terms to the left:
12+5x-(22+3x*)=0
We add all the numbers together, and all the variables
5x-(3x*+22)+12=0
We get rid of parentheses
5x-3x*-22+12=0
We add all the numbers together, and all the variables
5x-3x*-10=0
We move all terms containing x to the left, all other terms to the right
5x-3x*=10
| 7(2w-1)=-3 | | x+10+x+10+8x=180 | | 6q+10=4q | | 4(7x-3)=9 | | X+4/14+x-4/6=2 | | (7e+5)/e=26/3 | | -10x-3+2x=4x=21 | | 17x-10-16x=4 | | -2=v+(-15) | | 8-(-6u+9)=-3u+1 | | 2-7(6h+5)=-3h-2 | | 5x-20-6=4x-12 | | 3x-2x=-5+5 | | 24x-34=5x-2 | | 5(a-1)+2(a+3)+6=0 | | 10x+2=8x+6 | | 20x-18=19x+1 | | 10^x=610 | | 10x=610 | | 8(x+2)+4=-2(x-9)-5 | | X2+4x-37=0 | | 7(x-5)-1=4(x+3) | | X-1/8=1+x+1/18 | | 255=8(s-65)+55 | | -9x-8=-5 | | 2x^{2}-4x-9=0 | | -2y-7(7y+8)=-1-8(-6-y) | | -2(-2-y)-y-2=0 | | 7(-5p+8)=196 | | X-4/7=x-10/5 | | 5(x+8)=2(x+9) | | -5(x-2)+7=-4(x+5) |